(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
The aim of this paper was to attain best optimization for twist angle and the chord of wind mill blade by using CFD code with Schmitz, Betz and .Lift to drag twist optimization along with Genetic Algorithm method. The technical point of view to change the cross section of the blade by using symmetry airfoil (NACA-0012), unsymmetrical airfoil (NACA-4412) and supercritical airfoil (Eppler-417). The best optimization Method was Schmitz chord optimization and lift to drag for twist optimization which increase the Cp 10.3% for Eppler 417 , 9.5% for NACA 4412 and 16% for NACA 0012. All results were plotted and tabulated for all optimization results.